Split spin-squeezed Bose–Einstein condensates. (19th September 2019) - Jing, Yumang; Fadel, Matteo; Ivannikov, Valentin; Byrnes, Tim
Abstract: We investigate and model a method for producing entanglement between two spatially separated Bose–Einstein condensates (BECs). In our approach, a spin-polarized BEC is squeezed using a ( S z ) 2 interaction, then are split into two separate clouds. After the split, we consider that the particle number in each cloud collapses to a fixed number. We show that this procedure is equivalent to applying an interaction corresponding to squeezing each cloud individually plus an entangling operation. We analyze the system's inter-well entanglement properties and show that it can be detected using correlation-based entanglement criteria. The nature of the states is illustrated by Wigner functions and have the form of a correlated squeezed state. The conditional Wigner function shows high degrees of non-classicality for dimensionless squeezing times beyond 1 / N, where N is the number of particles per BEC.